The Influence Of Earnings Per Share, Net Profit Margin And Return On Equity On Stock Prices At PT. Hanjaya Mandala Sampoerna, Tbk. Year 2014 – 2023 - Ismiyah, Hayatul; Jamaludin, Jamaludin (Fin Sinergy: Jurnal Manajemen Keuangan, 2025)
This study analyzes the influence of Earning Per Share (EPS), Net Profit Margin (NPM), and Return On Equity (ROE) on the stock price of PT Hanjaya Mandala Sampoerna Tbk for the period 2014-2023 using a descriptive quantitative method. The research sample was selected using a purposive sampling technique, and data analysis included classical assumption tests, multiple regression analysis, and hypothesis testing (t-test, F-test, and coefficient of determination test). The t-test results show that EPS (sig. 0.435 > 0.05; t-value 0.836 < t-table 2.447) and ROE (sig. 0.259 > 0.05; t-value -1.245 < t-table 2.447) do not significantly affect stock prices, whereas NPM (sig. 0.006 < 0.05; t-value 4.164 > t-table 2.447) has a significant influence. The F-test (sig. 0.021 < 0.05; F-value 7.064 > F-table 4.76) indicates that EPS, NPM, and ROE collectively impact stock prices.